2015
DOI: 10.1016/j.archger.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-reported ill health among older Ugandans: A cross sectional study

Abstract: HighlightsWe estimate the prevalence of self-reported ill health among older people in Uganda.Cross sectional national survey data of 2382 older persons is used.Most (62%) older Ugandans reported ill health.The women, oldest old, household heads, Catholics reported poorer health.Those with non-communicable diseases (NCDs) and disability reported poor health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 45 publications
7
24
0
Order By: Relevance
“…Other studies highlight that women over-report worse health status than men [41][42][43][44]. Various authors have argued that women are more sensitive, interface with the healthcare system as caregivers of their children and easily report health conditions than men [43,44]. In our study, we found that the large gender disparities are confined to rural areas and absent in urban areas.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Other studies highlight that women over-report worse health status than men [41][42][43][44]. Various authors have argued that women are more sensitive, interface with the healthcare system as caregivers of their children and easily report health conditions than men [43,44]. In our study, we found that the large gender disparities are confined to rural areas and absent in urban areas.…”
Section: Discussionsupporting
confidence: 51%
“…Several studies argue that poorer health among women is due to biological as well as behavioural factors and cannot be explained by differences in socio-economic and demographic factors only [4,[40][41][42]. Other studies highlight that women over-report worse health status than men [41][42][43][44]. Various authors have argued that women are more sensitive, interface with the healthcare system as caregivers of their children and easily report health conditions than men [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Featured research topics in Figure 5 were based on the top cited publications from each income group in each year: high–income countries [2,13,2336], upper–middle income countries [8,37–45], lower-middle income countries [7,9,4650], and low–income countries [5153]. …”
Section: Resultsmentioning
confidence: 99%
“…Different vulnerability indicators were tested on the 1991 and 2002 population census data (Antoine and Golaz 2011; Golaz and Rutaremwa 2011). Disabilities and ill health among older people were obtained using Uganda National Household Survey (UNHS) data (Wandera et al 2014, 2015). Perceptions related to old age (Najjumba-Mulindwa 2003) and the feeling of loneliness among older people (Nzabona, Ntozi and Rutaremwa 2015) were analysed through specific quantitative surveys in different parts of the country.…”
Section: Vulnerability and Resilience In The Ugandan Contextmentioning
confidence: 99%